Toward Equitable Digital Mental Health: Integrating AI and Telepsychiatry in Global Practice - Algristian, Hafid; Sitorus, Anwar T (Indonesian Scientific Publication, 2024)
In response to the growing mental health crisis and the expansion of digital healthcare, this narrative review explores the application of telepsychiatry and artificial intelligence (AI) in mental health services. The study aims to synthesize recent developments, challenges, and future directions in digital mental health innovation. A systematic literature search was conducted across PubMed, Scopus, and Web of Science databases, focusing on studies published between 2016 and 2023. Keywords such as